The influence of stakeholder-firm power difference on corporate social responsibility of Chinese small and medium-sized enterprises. (2015) - Tang, Zhi; Tang, Jintong
Recent CSR research proposed the construct of stakeholder-firm power difference, that is, the net difference between a stakeholder's power over a firm and a firm's countering power to this stakeholder and established the significant role of stakeholder-firm power difference in firms' environmental performance. Extending this line of research and drawing upon the framework of basic institutional prerequisites for CSR, we investigate how regional economic development, state ownership, neo-Confucian business style and entrepreneurial orientation impact the relationship between stakeholder-firm power difference and CSR engagement of Chinese SMEs. Implications of our propositions and suggestions for future research are offered in the end.